2015
DOI: 10.2217/bmm.14.100
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-To-Lymphocyte Ratio is a Marker of Poor Prognosis in Patients With Diabetes Mellitus and ST-Elevation Myocardial Infarction

Abstract: PLR proved to have good prognostic value for in-hospital and late mortality. PLR cut-off value for predicting in-hospital mortality was higher to that predicting late mortality. PLR remained an independent risk factor early and late mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 32 publications
2
44
0
1
Order By: Relevance
“…We identified PLR to have a moderate-togood prognostic value for in-hospital (AUC 0.61 (95% CI 0.56-0.65) P = 0.006) and late mortality (AUC 0.77 95% CI 0.73-0.80 P b 0.0001). In multivariate analysis, PLR remained an independent factor of long-term mortality (HR 1.08 95% CI: 1.03-1.12 P b 0.0001) (Hudzik et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…We identified PLR to have a moderate-togood prognostic value for in-hospital (AUC 0.61 (95% CI 0.56-0.65) P = 0.006) and late mortality (AUC 0.77 95% CI 0.73-0.80 P b 0.0001). In multivariate analysis, PLR remained an independent factor of long-term mortality (HR 1.08 95% CI: 1.03-1.12 P b 0.0001) (Hudzik et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…Thus far, many authors reported a high admission PLR to be a significant predictor short-and long-term mortality in patients with acute coronary syndromes (Cho, Ann, Singh, Her, & Shin, 2015;Cicek et al, 2015;Hudzik et al, 2015;Ozcan Cetin et al, 2016;Toprak et al, 2015). Ozcan Cetin et al examined PLR prognostic value on in-hospital and long-term MACE (stent thrombosis, nonfatal myocardial infarction, and mortality) in patients with STEMI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 Current studies have reported that higher PLR values were associated with the no-reflow phenomenon, increased SYNTAX score, impaired infarct artery patency, and worsening in-hospital and short-term outcomes in STEMI. 8,[11][12][13][14][15][16] There is no comprehensive study investigating the importance of this parameter on long-term major adverse cardiovascular events (MACE) in this population. Therefore, we assessed the prognostic value of PLR on inhospital and long-term MACE in patients with STEMI undergoing primary percutaneous coronary intervention (pPCI) in a large prospective study.…”
Section: Introductionmentioning
confidence: 99%